228k views
0 votes
What is the rule for the function shown in the table?

Input x -2 -1 0 1 2

Output y -8 -5 -2 1 4


y = 2x – 2
y = x – 6
y = 4x
y = 3x - 2

User Huseyint
by
5.5k points

2 Answers

5 votes

Answer:

the answer is the last one.

솓 묹ㄷㄱ ㅑㄴ 솓 ㅣㅁㄴㅅ ㅐㅜㄷ.

Explanation:

y= 3x-2

ㅛ=3ㅌ-2

hope this helped!!!

ㅙㅔㄷ 소ㅑㄴ ㅗ디ㅔㄷㅇ!!!

User Jiminy
by
5.5k points
1 vote

its following y = 3x -2

pur the value of x in this to get value of y and verify. it should satisfy the table

User Tahmina Khatoon
by
6.0k points